Valuing marine plankton: a review of ecosystem services and disservices and an expert assessment of the potential of area-based protection - Eva Wanek; Oscar Julian Esteban-Cantillo; Sacha Bourgeois-Gironde; Sacha Bourgeois-Gironde; Sacha Bourgeois-Gironde (Frontiers in Marine Science, 2025)
Marine plankton play a crucial yet understudied economic role, contributing both positively through ecosystem services (ES) and negatively through ecosystem disservices (EDS). This study employs a mixed-methods approach to address key research gaps in plankton valuation and plankton value-based policy optimization. We (i) conduct a semi-systematic review of marine plankton ES and EDS and their economic assessments, and (ii) develop an expert assessment tool to evaluate the expected effects of marine policy on plankton ES and EDS and apply it to a hypothetical fully protected marine area. Our review reveals that while plankton ES are increasingly recognized and classified, their economic valuation remains scarce due to their indirect and diffuse economic impacts. In contrast, plankton EDS, though not previously comprehensively classified as such, have been more extensively quantified, as their economic costs are typically localized and more directly attributable. The expert assessment, conducted with 19 marine scientists (including eight plankton specialists), highlighted the potential of marine protection to enhance research opportunities, support plankton’s role in marine food webs and fish larvae recruitment, and mitigate harmful algal blooms (HABs). However, experts also noted significant uncertainties, particularly due to the high spatial variability and mobility of plankton. Our findings underscore the need for comprehensive assessments of the cumulative social benefits of regulating ES beyond carbon sequestration to better capture plankton’s economic significance. Additionally, we advocate for more spatio-temporally flexible conservation approaches to account for plankton dynamism in marine policy and management.